Similarity of fine specificity of IgA anti-gliadin antibodies between patients with celiac disease and humanized α1KI mice - Sánchez, Daniel; Champier, Gaël; Cuvillier, Armelle; Cogné, Michel; Pekáriková, Aneta; Tlaskalová-Hogenová, Helena; Hoffmanová, Iva; Drastich, Pavel; Mothes, Thomas; Tučková, Ludmila (Journal of agricultural and food chemistry, 2011)
Gliadins, and primarily α-gliadins containing several sequences such as aa 31-49, aa 56-88 (33-mer), aa 57-68, and aa 69-82, are critical in the induction of immune response or toxic reaction leading to the development of celiac disease (CLD). The role of IgA anti-gliadin antibodies (IgA AGA) is unknown. To this end, we prepared several humanized monoclonal IgA AGA using transgenic α1KI mice. Employing Pepscan with overlapping decapeptides of α-gliadin we observed a robust similarity between the specificity of humanized mouse monoclonal IgA AGA and IgA AGA from patients with florid CLD. The common immunodominant region included several sequential epitopes localized in the N-terminal part of α-gliadin (QFQGQQQPFPPQQPYPQPQPFP, aa 29-50, and QPFPSQQPYLQL, aa 47-58). Notably, IgA AGA produced by clones 8D12, 15B9, 9D12, and 18E2 had significant reactivity against sequences localized in the 33-mer, LQLQPFPQPQ (aa 56-65) and PQLPYPQPQPFL (aa 69-80). Humanized mouse monoclonal IgA AGA that have a known specificity are suitable as standard in ELISAs to detect serum IgA AGA of CLD patients and for studying the AGA pathogenic role in CLD, especially for analyzing the translocation of complex of specific IgA antibodies and individual gliadin peptides through enterocyte barrier.
Keywords: Mice, Transgenic; molekulární sekvence - údaje; Epitopes; Adolescent; specificita protilátek; zvířata; Antibodies, Monoclonal; Animals; epitopy; lidé; Adult; myši transgenní; dospělí; Antibody Specificity; Molecular Sequence Data; gliadin; Female; Mice; Gliadin; imunoglobulin A; sekvence aminokyselin; Amino Acid Sequence; Male; ženské pohlaví; Immunoglobulin A; Humans; mužské pohlaví; Celiac Disease; myši; celiakie; monoklonální protilátky; mladiství